Cooperative design, visualization, and engineering : 15th International Conference, CDVE 2018, Hangzhou, China, October 21-24, 2018, Proceedings /: 15th International Conference, CDVE 2018, Hangzhou, China, October 21-24, 2018, Proceedings. (2018) - Unknown
No abstract available